1990
DOI: 10.1128/iai.58.3.619-624.1990
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and bacteriology of sepsis following cecal ligation and puncture in aged mice

Abstract: Epidemiologic data suggest that elderly adults are more susceptible to invasive bacterial infection by indigenous gut flora than are younger adults. The purpose of this investigation was to characterize a murine model of clinically encountered peritonitis in the aged. We subjected three different age groups (young, 16 weeks; mature, 12 months; senescent, 24 months) of C57BL/6NNia mice to surgically induced peritonitis by the cecal ligation and puncture procedure. Senescent mice died in a significantly shorter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…CLP surgical procedure. Peritonitis was induced surgically as described previously (20). Briefly, a 1-cm incision was made into the peritoneal cavity, and the cecum was exposed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CLP surgical procedure. Peritonitis was induced surgically as described previously (20). Briefly, a 1-cm incision was made into the peritoneal cavity, and the cecum was exposed.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous investigation, we used the cecal ligation and puncture (CLP) procedure to compare age-related differences in lethality of overwhelming bacterial infection (20,44). We found that senescent (24-month-old) C57BL/6NNia male mice subjected to CLP sepsis were more sensitive than mature (12-month-old) mice as manifested by significantly shorter survival times after surgery (means, 24 and 38 h, respectively) and a 100-fold-lower bacterial burden at the time of death.…”
mentioning
confidence: 99%
“…The generated cytokine levels and overall physiology of the animals are closer to what is observed in most patients [13,14]. Furthermore, the presence of actual bacteria in the blood as opposed to chemically purified endotoxin somehow changes the pathophysiology of the disease [15]. This is clearly illustrated in the mortality rate of animals with absent TLR4 when subjected to either model [no effect with lipopolysaccharide (LPS) injection but significant mortality with CLP] [16,17].…”
Section: Animal Models Of Systemic Sepsismentioning
confidence: 76%
“…The role of specific TLRs should be investigated with caution in CLP as it is essentially a polymicrobial model of sepsis, albeit with a predominance of gram-negative contribution [15]. Nevertheless, and despite technical difficulties that can result in a lack of consistency, this model is gaining increased use because of its superior clinical relevance [10].…”
Section: Animal Models Of Systemic Sepsismentioning
confidence: 99%
“…In both the models, azithromycin neither elevated nor further suppressed the WBC count, thus suggesting it to have no immunosuppressive property. Sepsis is reported to produce hypodynamic state by reducing body temperature and blood glucose (19). Therefore these parameters were measured in all the groups.…”
Section: Discussionmentioning
confidence: 99%